Pelatihan dan Pendampingan Pembuatan Kombucha Salak Bali Kelompok Tani Mekar Sari, Sibetan, Karangasem, Bali - Dylla Hanggaeni Dyah Puspaningrum; I Gusti Ayu Ika Monika Prastyandhari; I Wayan Ruspendi Junaedi; I Gusti Ayu Agung Sinta Diarini (I-Com: Indonesian Community Journal, 2024)
The abundance of salak during the harvest period (January to March) causes the selling price of salak bali to drop to the lowest price of Rp. 1,000/kg and the unsold products will remain rotting in the garden. Making processed products from salak is one alternative way to increase the use value of salak. Seeing these problems in order to utilize the abundant harvest and help increase farmers' income, it is necessary to carry out community service focused on providing knowledge and skills in the processing of salak. This activity aims to provide training and assistance in processing salak into fermented salak drink (kombucha salak) to salak farmer groups. Community service activities begin with conducting a preliminary survey, which is then continued with training and assistance in making fermented salak beverage products. In the process, information and knowledge transfer was carried out followed by filling out a questionnaire. The results of this community service activity show that most of the participants have a good level of understanding of probiotic drink information, implementation of processing sanitation hygiene, the right way to make fermented salak drink. The results of the program sustainability questionnaire show that partners need further assistance regarding training in making more diverse salak processed products, counseling related to clinical information on nutrition and nutrition, effective product marketing strategies both online and offline.